2000
DOI: 10.4269/ajtmh.2000.63.76
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Parasight-F diagnostic test for imported malaria in a travel clinic.

Abstract: Abstract. The Parasight-F test based on the detection of a soluble antigen specific for Plasmodium falciparum is designed for the immediate diagnosis of malaria infection. We evaluated its use by clinicians during consultations. This prospective study of its diagnostic utility in febrile patients consulting a travel clinic on their return from areas endemic for malaria was conducted between May 1996 and May 1997. The Parasight-F test was performed by the clinician with confirmation by means of standard microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
1
0
1
Order By: Relevance
“…(Miller et al 1994;Cerutti et al 1999) in Egyptian and Sudanese mummies (4150 years BP) has been reported with up to 35-40% positivity for malaria. In these cases, however, unspecific reactions of the antibodies used in the test have raised questions about the reality of the recovered frequencies of the disease (Bouchaud et al 2000). The sole detection of a helminth using immunological techniques was reported by Deelder et al (1990), with the detection using ELISA of S. haematobium from an Egyptian mummy dated to 5150 years BP.…”
mentioning
confidence: 99%
“…(Miller et al 1994;Cerutti et al 1999) in Egyptian and Sudanese mummies (4150 years BP) has been reported with up to 35-40% positivity for malaria. In these cases, however, unspecific reactions of the antibodies used in the test have raised questions about the reality of the recovered frequencies of the disease (Bouchaud et al 2000). The sole detection of a helminth using immunological techniques was reported by Deelder et al (1990), with the detection using ELISA of S. haematobium from an Egyptian mummy dated to 5150 years BP.…”
mentioning
confidence: 99%
“…Prema dosadašnjim kliničkim ispitivanjima, senzitivnost testa je iznosila od 86.7% do 93.4%, a specifičnost od 98.2% do 99.3%. Tehnika PCR je senzitivna (više od 90%) i visoko specifična (100%), ali se uglavnom ne koristi u rutinskoj, kliničkoj dijagnostici, već prevashodno u istraživačke svrhe (33,34,35).…”
Section: Klinička Slika I Dijagnozaunclassified